THE HISTORICAL CONTEXT AND AREAS OF INFLUENCE OF INTERNAL COMBUSTION ENGINES - Voutsinas , Panagiotis; Wergin, Andreas; Dimitroulis, Thanos (Open Schools Journal for Open Science, 2025)
The paper herein provides a detailed historical overview of internal combustion engines (ICEs), from the early concepts to modern developments. The evolution of ICEs in the 19th century was a key development in industrial advancement, which enabled expansion in industries like transportation, manufacturing, and agriculture. Important persons like Nikolaus Otto and Rudolf Diesel created revolutionary technologies that changed energy production and use. This research analyzes the revolutionary influence of ICEs on global integration and economic development, enumerating the achievements and unresolved challenges in balancing performance and the environment.